2019
DOI: 10.5430/wje.v9n2p123
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Culture, Commitment and Job Satisfaction of Faculty in Private-Sectarian Higher Education Institutions (HEIs)

Abstract: This study explored the organizational culture, organizational commitment and job satisfaction of the faculty membersof the St. Paul University System (SPUS). This study employed a descriptive and correlational research design. Thedata gathered were analyzed and interpreted using frequency and percentage distribution to confirm statisticalassumptions and to describe the participants' profile in terms of the identified variables. The weighted mean was usedto interpret the responses obtained from the use of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…Similarly, other scholars addressed organizational structure and employee commitment of academic staff in private university (Magizi, et al, 2019); affective commitment of academics in university (Nkhukhu Orlando, et al, 2019) impact of continuance commitment to job performance (Kosogela, 2019): organizational trust employee commitment and job satisfaction (Gider, et al, 2019); Employees commitment and its impact in organizational performance (Andrew,2017); organizational culture, commitment and job satisfaction (Batugal, 2019); and, effect of strategic management and organizational commitment on employees work achievement (Rustamadji and Omar, 2018). Yet it was observed that these studies did not examine perceived leadership styles, nor organizational commitment on job satisfaction among non-teaching employees of Federal universities in South-East Nigeria.…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, other scholars addressed organizational structure and employee commitment of academic staff in private university (Magizi, et al, 2019); affective commitment of academics in university (Nkhukhu Orlando, et al, 2019) impact of continuance commitment to job performance (Kosogela, 2019): organizational trust employee commitment and job satisfaction (Gider, et al, 2019); Employees commitment and its impact in organizational performance (Andrew,2017); organizational culture, commitment and job satisfaction (Batugal, 2019); and, effect of strategic management and organizational commitment on employees work achievement (Rustamadji and Omar, 2018). Yet it was observed that these studies did not examine perceived leadership styles, nor organizational commitment on job satisfaction among non-teaching employees of Federal universities in South-East Nigeria.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Results of the study indicated that employees commitment (Affective, Normative, continuance) are significantly related to organizational performance in Eravupatru Divisional Secretariat. Batugal (2019) reported a study on organizational culture, commitment and job satisfaction of faculty in private-Sectarian Higher Education Institute (HEIS). Descriptive and correlation research design were employed in the study.…”
Section: Review Of Raelated Literaturementioning
confidence: 99%
“…Moreover, Abasilim, Gberevbie, and Osibanjo (2019) define organizational commitment as employee behaviour in order for the organization to be able to spend time on organizational matters, to build good relations with colleagues, and to have passion for hard work. Additionally, Batugal (2019) points out that commitment is demonstrated by referring to the hard work of lecturers at a higher education institution in St. Thomas, The University of Paul, Philippines. On the other hand, Jawaad, Amir, Bashir, and Hasan (2019) suggest that emotional satisfaction in working relationships, as well as employee engagement with the company, represent dedication.…”
Section: ) Internalized Moral Perspectivementioning
confidence: 99%
“…They also discovered that when an individual is actively involved, it can be impossible for them to give up their principles in the organization. Studies have found that dedicated workers contribute to healthy output and efficiency (Batugal, 2019). Nevertheless, owing to the poor skills of executive management, most workers neglect their emotions, passion, dedication, and participation in their jobs, and this has influenced their organizational success (Sakic, Hadziahmetovic, & Tandir, 2019).…”
Section: Research Problemmentioning
confidence: 99%
“…Creating an organizational culture respects every organization member and effectively produces a higher level of organizational commitment. It produces higher levels of organizational commitment and job satisfaction (Batugal, 2019).…”
Section: Introductionmentioning
confidence: 99%